Cross-national Macro Analysis of Household Expenditures for Daily Mobility: An Exploratory Study in Europe - Anna URBANEK (Communications of International Proceedings, 2021)
Passenger cars are the dominating means of transport used for daily mobility in a majority of countries and cities around the world. Such modal division has negative consequences for the natural environment and the quality of life. The sustainable mobility policy requires understanding the motives behind transport behaviours at the level of individual traveller and household, i.e. at the microeconomic level, as well as the differences and conditions occurring at the macroeconomic level, i.e. in particular countries. The article examines the preferences of households regarding the methods of fulfilling the daily transport needs. The research was performed on the basis of the analysis of household expenditure for transport, and in particular for the purchase and use of passenger cars, as well as expenditure for transport services. The study uses a macroeconomic approach and was carried out on a macro scale, using aggregated data for 29 European countries. The analysis covers the period from 2000 to 2019. The research is exploratory and can be used as a starting point for further in-depth research.
Keywords: Households; expenditure; transport; macro analysis; mobility; commuting.